Novel micronutrient associations in homocysteine metabolism - Krishnamurthy, Hari K; Reddy, Swarnkumar; Jayaraman, Vasanth; Krishna, Karthik; Song, Qi; Wang, Tianhao; Bei, Kang; Rajasekaran, John J (Progress in Nutrition, 2023)
AbstractObjective: Elevated serum levels of homocysteine are one of the most effective biomarkers in diagnosing atherosclerotic cardiovascular disease and associated disorders. The elevated levels of homocysteine may result from mutations in genes coding vital enzymes or other environmental factors such as nutrition, medications, increased methionine intake, pregnancy, etc.Methods: The association of 36 vital micronutrients with circulating levels of homocysteine in a population of 336 free-living individuals was analyzed. Baseline serum homocysteine concentration was measured by enzyme-linked immunosorbent assay using Beckman Counter AU series Analyzers.  Results: Non-parametric analysis by Mann-Whitney U test as well as Pearson’s correlation showed a strong association of vitamin B9 (folate) and vitamin B12 with high serum levels of homocysteine. Interestingly several amino acids including asparagine, isoleucine, cysteine, citrulline, and carnitine exhibited a positive correlation with serum homocysteine. Among vitamins and minerals, vitamin A and selenium were positively correlated with circulating homocysteine.Conclusion: The study suggests that the serum levels of several micronutrients act as confounding variables in regulating the circulating levels of homocysteine. Several novel nutrient associations for modulating levels of homocysteine are highlighted.  Given that homocysteine is a modifiable risk factor, these nutrients could play an important role in preventive care settings and should be further investigated clinically.